1987
DOI: 10.1128/jb.169.6.2523-2528.1987
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the sppA gene coding for protease IV, a signal peptide peptidase of Escherichia coli

Abstract: The sppA gene codes for protease IV, a signal peptide peptidase of Escherichia coli. Using the gene cloned on a plasmid, we constructed an E. coli strain carrying the ampicillin resistance gene near the chromosomal sppA gene and an sppA deletion strain in which the deleted portion was replaced by the kanamycin resistance gene. Using these strains, we mapped the sppA gene at 38.5 min on the chromosome, the gene order being katE-xthA-sppA-pncA. Although digestion of the signal peptide that accumulated in the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…The sppA gene codes for protease IV, a signal peptide peptidase found in the cytoplasmic membrane that digests cleaved signal peptides (13,36). The sppA gene is also not essential for bacterial growth (36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sppA gene codes for protease IV, a signal peptide peptidase found in the cytoplasmic membrane that digests cleaved signal peptides (13,36). The sppA gene is also not essential for bacterial growth (36).…”
Section: Resultsmentioning
confidence: 99%
“…The sppA gene codes for protease IV, a signal peptide peptidase found in the cytoplasmic membrane that digests cleaved signal peptides (13,36). The sppA gene is also not essential for bacterial growth (36). Bacteria which carry a deletion of the gene digest signal peptides at a considerably slower rate than sppA+ bacteria, although this digestion is still significant (36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For prokaryotes in general, little is known about the removal of signal peptides from the membrane. E. coli SppA (protease IV) has been shown to degrade the processed signal sequence of the major lipoprotein, but it is not the only protease that is responsible for signal peptide digestion in the cell envelope (Suzuki et al, 1987). For B. subtilis, three proteins similar to SppA have been described (TepA, SppA and YqeZ; Bolhuis et al, 1999;Helmann, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that a membrane-bound protease SppA degraded SP from Lpp in detergent extracts (15,16). However, its in vivo function has not been established.…”
Section: Rsep Cleavage Of Sp Requires a Preceding Processing Of Preprmentioning
confidence: 99%